2022
DOI: 10.18805/ijare.a-6009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depth of Sowing and Mulching on Rainfed Chickpea (Cicer arietinum) in Red and Lateritic Belt of West Bengal

Abstract: Background: Availability of soil moisture is a serious bottleneck for successful growing of post monsoon crops in red and lateritic soil. Hence, soil moisture conservation is crucial for post monsoon crops. In this aspect using mulches for conservation of moisture and optimum depth of sowing for proper germination and seedling emergence are important crop management practices in red and lateritic soil. Methods: The experiment was laid out in split plot design with three depths of sowing as main-plot treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Similar trends were observed for interaction effects of varieties × sowing dates on incidence, AUDPC, and the disease progress rate at both locations. Likewise, Yigrem et al ( 2018), Kemal et al (2015), and Biswas & Ali (2017) confirmed strong influence of varieties and sowing dates on disease parameters.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Similar trends were observed for interaction effects of varieties × sowing dates on incidence, AUDPC, and the disease progress rate at both locations. Likewise, Yigrem et al ( 2018), Kemal et al (2015), and Biswas & Ali (2017) confirmed strong influence of varieties and sowing dates on disease parameters.…”
Section: Discussionmentioning
confidence: 79%
“…(2018), Kemal et al. (2015), and Biswas & Ali (2017) confirmed strong influence of varieties and sowing dates on disease parameters.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation